Creation, Innovation, Technology and Research Exposition (CITREX) - UMP, PNC (Penerbit UMP, 2015)
A university that is described as a school of universal learning actually advocates a much bigger role and obligation. It is not only an institution of knowledge but it also has a wider dimension that refers to the process of dissemination.